Ethylene-bridged asymmetric cavitands as building blocks for supramolecular polymers and capsules. Issue 39 (19th August 2016) - Aakeröy, Christer B.; Chopade, Prashant D.; Desper, John
Abstract : A supramolecular polymer as well as a dimeric capsule, both constructed from a combination of a tetra-carboxylic acid functionalized cavitand and a suitable N-heterocyclic 'linker', have been crystallographically characterized. Abstract : A supramolecular polymer as well as a dimeric capsule, both constructed from a combination of a tetra-carboxylic acid functionalized cavitand and a suitable N-heterocyclic 'linker', have been crystallographically characterized.